Avec Mauss et Polanyi, vers une théorie de l'économie plurielle - Laville, Jean-Louis (Revue du MAUSS, 2003)
Mauss and Polanyi sketched the theoretical foundations of a pluralist approach to the economy and began a reflection on social change that was not satisfied with the ritual evocation of a reversal of the system. In other words, instead of an abstract call to an alternative economy, the concrete path of "altereconomies" opens the field of possibilities.
Keywords: altereconomies